Aliceheimer's : Alzheimer's through the looking glass - Walrath, Dana; Walrath, Dana. (University Park, Pennsylvania : The Pennsylvania State University Press, 2016)
"A graphic memoir of the author's experiences of her mother's battle with dementia. Illustrates the two-way nature of storytelling as a process that heals both the giver and the receiver of story"--Provided by publisher.
Reprint of: Aliceheimer's / Dana Walrath. Yerevan, Armenia, Harvest Publishers, 2013.
JSTOR
Keywords: Alzheimer's disease; Mother and child; Alzheimer Disease; Caregivers -- psychology; Mother-Child Relations; Maladie d'Alzheimer.; Mère et enfant; HEALTH & FITNESS / Diseases & Conditions / Alzheimer's & Dementia; Alzheimer's disease; Mother and child; Electronic books; Graphic Novel; Personal Narrative; Popular Work; graphic novels; Graphic novels; Personal narratives; Graphic novels; Personal narratives; Romans graphiques; Récits personnels